Controlled Impact Technique for the Correction of the Verticality of Part-Collapsed Buildings with Semi-Compensated Foundations in the Lake Zone of Mexico City - Barraza, Julio A. (European Journal of Applied Sciences, 2024)
The article presents a new technique for the correction of the verticality of partcollapsed buildings in the lake zone of Mexico City, the technique was conceived from the study of the deformation properties of the Mexico city subsoil and the behavior of the clays deposits of this city under cyclic loads, for buildings with similar foundations geometry that presents complex problems of differential settlements in this geotechnical zone. The problematic and properties of the subsoil where analized to desing this technique that use mechanics procedures and geotechnical machines and conditions of load that are representable with laboratory. Also is presented a theoretical analysis of the condition of load for the process of this technique and the technical aplication procedure.